Neutrons in soft matter - Imae, Toyoko (Hoboken, N.J. : J. Wiley, 2011)
"Car windshields, credit cards, calculators, food packaging, and countless other items have seen improvement in quality thanks to neutron research. Essentials of Neutron Techniques for Soft Matter addresses instrumental techniques related to neutron and synchrotron study and, in particular, small-angle-neutron scattering, which can reveal how long, threadlike polymer molecules pack to give plastics their diverse properties. Recognizing that new neutron sources are about to be constructed around the world, this book serves as a valuable guidebook for scientists that will be trained to use and conduct experiments at such facilities"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Neutrons -- Scattering; Soft condensed matter; Electronic books